ANALISIS PUBLIC PRIVATE PARTNERSHIP DALAM PENGEMBANGAN DESTINASI WISATA DI DESA WISATA CONTO KABUPATEN WONOGIRI - Aurel Lisa, Chetrin; Hanani, Retna; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
This research aims to analyze Public Private Partnerships in developing tourist destinations in the Conto Tourism Village, Wonogiri Regency and analyze the success factors of Public Private Partnerships. The author uses the theory of Public Private Partnership principles according to Satyanaryama and Yescombe and analyzes factors according to Kurniadi's theory. The research method uses a qualitative approach with data collection techniques in the form of observation, interviews and documentation. The results of the research are that the principles of public private partnership in developing tourist destinations in the Conto Tourism Village, Wonogiri Regency are not yet fully optimal. The principle of partnership in village government collaboration with the private sector is based on an MOU for the use of village treasury land. The principle of benefit is carried out through the provision of infrastructure carried out by both parties which can be beneficial for the people of Conto Village. The principle of competition in this collaboration does not apply the principle of competition. Principles of risk control and management in partnerships are carried out optimally through mitigation and management stages. The principle of effectiveness is carried out in village government partnerships with the private sector, seen from the clarity of programs in accordance with common goals and improving the quality of services in infrastructure management and maintenance. Efficient Principles in partnerships, this collaboration has an effective principle, namely that the provision of existing infrastructure is able to accelerate development in the village as well as improve infrastructure management and maintenance. Success factors include government capability, opportunistic behavior, attractive rewards, legal certainty, and PPP institutions. The success factor that was not implemented was the institutional public private partnership.